Using the Beveridge & Nelson decomposition of economic time series for pointing out the occurrence of terrorist attacks - Gómez-Sorzano, Gustavo
This paper continues my research program on violence and terrorism started 15 years ago. It presents in the first part through empirical exercises, the suitability of The Beveridge and Nelson decomposition of economic time series for pointing out the occurrence of terrorist attacks. It presents the simulation results of the hypothetical case of U.S., and Colombia experiencing, additional, and first three terrorist attacks similar to 9/11, 2001: for the U.S. additional attacks are simulated occurring in 1996, and 1998 with 24,950, and 61,516 casualties respectively; while for Colombia three attacks are artificially constructed independently in 1993 with 3,000 casualties, and 2001 with alternatives scenarios of 3,000 and 4,299 casualties. In the second part, while the model for terrorist attacks in U.S. soil is developed, and knowing that the geo-political context of the war in Iraq is different, Its objective, is to use the experience from Colombia to help policy, and decision makers understand the probable outcomes and implications of decisions taken today in regards to the war in Iraq. It uses the terrorist murder and attacks indicator from 1946 to 2001 for Colombia that assumes a 9/11 in Colombia killing 3,000 civilians, and that as its consequence the Colombian army started a strong confrontation against the enemy as the U.S did at that time. This indicator is used as dependent variable to re-estimate the model for cyclical terrorist murder for Colombia (Gómez-Sorzano 2006B, http://mpra.ub.uni-muenchen.de/539/01/MPRA_paper_539.pdf) using it, for sensitivity analysis scenarios including troop deployment decisions identical to those already taken by the U.S. during the war in Iraq. The last section concludes showing dynamically how at this point, moderate troop withdrawals and disarmament, will reduce both the intensity of the conflict and the estimated terrorist murder and attacks indicator for the U.S.United States; Colombia; cyclical terrorist murder; cyclical terrorist murder and attacks indicator; terrorist murder and attacks index; terrorist murder and attacks signal; model of cyclical terrorist murder for Colombia; model for terrorist attacks in U.S. soil